Does Cognitive Training Improve Mobility, Enhance Cognition, and Promote Neural Activation? - Marusic, Uros; Verghese, Joe; Mahoney, Jeannette R. (Frontiers in Aging Neuroscience, 2022)
A close inter-relationship between mobility and cognition is reported in older adults, with improvements in gait performance noticeable after cognitive remediation in frail individuals. The aim of this study was to evaluate the efficacy of computerized cognitive training (CCT) on mobility in healthy, independently living older adults, and to determine whether CCT is associated with changes in neural activation for mobility-related brain processes. Using a randomized single-blind control design, sixty-three non-demented adults age 60y and older (mean age=67y; 76% female, mean Montreal Cognitive Assessment [MoCA] score=27) were recruited from a local Senior Activity Center. Participants were randomly assigned to either a 2-month CCT program (8 weeks, 3x/week, 40 min/session) or a wait-list control group. Primary outcome was self-selected gait speed during single- and dual-task walking. Secondary outcome was executive function on Trail Making Test (TMT), Part B. Neural activity was assessed via electroencephalography/event-related potentials (EEG/ERPs) targeting lower-limb performance. Results from a linear mixed effect model, adjusted for baseline MoCA score, age, gender, and study completion revealed that compared to controls, CCT improved gait speed during the dual-task (p=0.008) but not during the single-task walking condition (p = 0.057). CCT also improved executive function (p=0.024). Further, shorter foot reaction time responses (p=0.019) were found with enhanced neural activation over sensorimotor areas, with shorter ERP latencies during the P2 component (p=0.008) and enhanced motor responses (p=0.009) also evident in the CCT group after the intervention. Overall, the electrophysiological findings suggest possible neural adaptations that could explain improvements in mobility and executive functions associated with CCT in healthy older adults.